Durability of CFRP cables exposed to simulated concrete environments. (4th May 2017) - Tanks, Jonathon; Sharp, Stephen; Harris, Devin; Ozyildirim, Celik
Abstract : One of the main causes of structural deficiency in concrete bridges is the deterioration of the constituent materials. Some transportation agencies have started exploring the use of carbon fiber reinforced polymers (CFRP) as a corrosion-resistant alternative to steel prestressing materials for longer lasting concrete bridge structures. To implement CFRP in prestressed concrete bridge structures with more confidence, an understanding of the challenges pertaining to durability under in-service environmental conditions is essential. This paper explores the effects of temperature with alkaline and alkaline/chloride solutions on material properties over time, in the context of reinforced and prestressed concrete structures for transportation applications. The durability testing yielded several key findings: (1) higher temperatures accelerate degradation, (2) moisture sorption was the primary process responsible for the observed degradation, with plasticization and microcracking as the controlling mechanisms leading to fiber–matrix interfacial debonding, and (3) a relaxation-based analytical model was implemented to predict residual properties after environmental exposure, showing promising agreement with experimental data.